Pelistega ratti sp. nov. from Rattus norvegicus of Hainan island. Issue 3 (10th March 2021) - Zhou, Xiaojun; Xuan, Duanduan; Hu, Shoukui; Du, Jiang; Pu, Ji; Jin, Dong; Zhao, Fan; Yin, Feifei; Cui, Xiuji; Huang, Yi; Wang, Gaoyu; Wu, Qiang; et al.
Abstract : Two strains (NLN63 T and NLN82) of Gram-stain-negative, oxidase- and catalase-positive, bacilli-shaped organisms were isolated from the faecal samples of two separate Rattus norvegicus in Baisha county of Hainan Province, Southern PR China. Phylogenetic analysis based on the near full-length 16S rRNA sequences revealed that strain NLN63 T belongs to the genus Pelistega, having maximum similarity to Pelistega suis CCUG 64465 T (97.1 %), Pelistega europaea CCUG 39967 T (96.2 %) and Pelistega indica DSM 27484 T (96.2 %), respectively. The phylogenomic tree built on 553 core genes from genomes of 20 species in the genus Pelistega and other adjacent genera further confirmed that strains NLN63 T and NLN82 form a distinct subline and exhibit specific phylogenetic affinity with P. europaea CCUG 39967 T . In digital DNA–DNA hybridization analyses, strain NLN63 T showed low estimated DNA reassociation values (21.4–22.6 %) with the type strains of the species in the genus Pelistega . The DNA G+C contents of strains NLN63 T and NLN82 were 37.3 and 37.1 mol%, respectively. Strain NLN63 T had a unique MALDI-TOF MS profile, contained Q-8 as the major quinone and C16 : 0, summed feature 8 (C18 : 1  ω 7 c /C18 : 1  ω 6 c or both) and summed feature 3 (C16 : 1  ω 7 c /C16 : 1  ω 6 c or both) as the dominant fatty acids. Based upon these polyphasic characterization data obtained from the present study, a novel species of the genus Pelistega, Pelistega ratti sp. nov., is proposed with NLN63 T (=GDMCC 1.1697 T =JCM 33788 T ) as the type strain.